Eye and Ear Temperature Using Infrared Thermography Are Related to Rectal Temperature in Dogs at Rest or With Exercise - Zanghi, Brian M. (Frontiers in Veterinary Science, 2016)
Rectal body temperature (BT) has been documented in exercising dogs to monitor thermoregulation, heat stress risk, and performance during physical activity. Eye (BTeye) and ear (BTear) temperature measured with infrared thermography (IRT) were compared to rectal (BTrec) temperature as the reference method and assess alternative sites to track hyperthermia, possibly to establish BTeye IRT as a passive and non-contact method. BT measures were recorded at 09:00, 11:30, 12:30, and 02:30 from Labrador Retrievers (N=16) and Beagles (N=16) while sedentary and with 30-min play-exercise (pre- and 0, 15, 30-min post-exercise). Total exercise locomotor activity counts were recorded to compare relative intensity of play-exercise between breeds. BTrec, BTeye, and BTear were measured within 5 min of the target time. Each BT method was analyzed by ANOVA for main effects of breed and time. Method differences were compared using Bland-Altman plots and linear regression. Sedentary BT differed by breed for BTrec (p<0.0001), BTear (p<0.0001), and BTeye (p=0.06) with Labs having on average 0.3-0.8oC higher BT compared to Beagles. Readings also declined over time for BTeye (p<0.0001) and BTear (p<0.0001), but not for BTrec (p=0.63) for both breeds. Total exercise (30-min) activity counts did not differ (p=0.53) between breeds. Time and breed interaction was significant in response to exercise for both BTrec and BTear (p=0.035 and p=0.005, respectively), with a marginal interaction (p=0.09) for BTeye. All 3 methods detected hyperthermia with Labs having a higher increase compared to Beagles. Both BTear and BTeye were significantly (p<0.0001) related to BTrec in all dogs with sedentary or exercise activity. The relationship between BTeye and BTrec improved when monitoring exercise hyperthermia (r=0.674) versus measures at rest (r=0.381), whereas BTear was significantly related to BTrec regardless of activity (r=0.615-0.735). Although BT readings were significantly related, method bias (p<0.02) was observed for BTeye to slightly underestimate BTrec, whereas no bias was observed between BTear and BTrec. This study demonstrates that IRT technology effectively measures both ear and eye temperature and enables effective monitoring of BT changes at rest, with exercise, and between breeds. However, ear, and not eye, temperature is a better reflection of rectal temperature.